A 4-year surveillance of antimicrobial resistance patterns of Acinetobacter baumanni in a university-affiliated hospital in China - Xu, Ting; Xia, Wenying; Rong, Guodong; Pan, Shiyang; Huang, Peijun; Gu, Bing (Journal of Thoracic Disease, 2013)
Objectives: To investigate the changes in resistance of Acinetobacter baumanni (A. baumannii) to different antimicrobial agents and the association of resistance rates with several independent factors: specimen origin, hospital wards, patients’ gender and age, from 2008 to 2011. Methods: Bacterial isolates were isolated from January 2008 to December 2011 in the First Affiliated Hospital of Nanjing Medical University. Antimicrobial susceptibility testing was determined by the Kirby-Bauer Disk Diffusion Agar method as recommended by CLSI. Data were managed by the software WHONET 5.4 and analyzed by SPSS 17.0 software. Results: The proportion of A. baumannii in our hospital increased from 7.0% in 2008 to 18.8% in 2011, becoming the most frequent pathogen in gram-negative isolates. 79.9% of A. baumannii were cultured from respiratory tract and geriatrics showed the highest isolation rate of A. baumannii during 4 years. The resistance rates to 12 antibiotics significantly increased from 2008 to 2011, from 14.8% to 90.8% to imipenem, and from 23.3% to 91.1% to meropenem. Statistical analysis demonstrated that the specimen origin, hospital wards, patients' gender and age were associated with resistance rate in varying degrees. Conclusions: The 4-year surveillance of antimicrobial susceptibility demonstrated the rapid increase of drug-resistant strains of A. baumannii, and revealed several factors related with resistance rate. Knowing the antimicrobial resistance patterns will help guide the empirical therapy and strengthen interventional infection control measures in China.